1989
DOI: 10.1161/01.hyp.14.3.304
|View full text |Cite
|
Sign up to set email alerts
|

Defective protein phosphorylation associated with hypofunctions in stroke-prone spontaneously hypertensive rat platelets.

Abstract: The mechanism of platelet dysfunctions in stroke-prone spontaneously hypertensive rats (SHRSP) was investigated. Platelet aggregation was inversely correlated with blood pressure or heart weight/body weight ratios in various strains of spontaneously hypertensive rats (SHR), indicating genetic defects. Thrombin-induced 47 kDa protein phosphorylation was markedly reduced in platelets of SHRSP compared with that in Wistar-Kyoto (WKY) rat platelets, accompanying reduced aggregation and secretion, but in 20 kDa pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 38 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…The hypofunction of platelets observed in SHRSP at the developmental ages of hypertension is of primary defect and is not secondary to the circulation of degranulated platelets (Umegaki et al 1986). It was also confirmed that the hypofunction was not rectified by a hypotensive treatment at the early hypertensive ages (Umegaki et al 1983). On the other hand, numerous investigations have shown that vascular reactivity to various Correspondence: T. Tomita, University of Shizuoka, Graduate School Accepted for publication 10 July 1995.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…The hypofunction of platelets observed in SHRSP at the developmental ages of hypertension is of primary defect and is not secondary to the circulation of degranulated platelets (Umegaki et al 1986). It was also confirmed that the hypofunction was not rectified by a hypotensive treatment at the early hypertensive ages (Umegaki et al 1983). On the other hand, numerous investigations have shown that vascular reactivity to various Correspondence: T. Tomita, University of Shizuoka, Graduate School Accepted for publication 10 July 1995.…”
Section: Introductionmentioning
confidence: 69%
“…We have previously reported that the magnitude of hypertension and the degree of platelet hypofunction were inversely correlated in WKY, SHRSP and FI (Tomita et al 1989). The hypofunction of platelets observed in SHRSP at the developmental ages of hypertension is of primary defect and is not secondary to the circulation of degranulated platelets (Umegaki et al 1986).…”
Section: Introductionmentioning
confidence: 91%